Body Image Dengan Harga Diri Pada Wanita Dewasa Awal Pengguna Skincare (Perawatan Wajah) - Windy Chintya Dewi; Erma Nursanti (Universitas Darul Ulum, 2022)
The purpose of this study is to determine the relationship between body image and self-esteem among young women growing up for skin care (facial treatments). The hypothesis is that there is a relationship between body image and self-esteem in young women who grow up doing skincare (face care) living in Jombang. These are all young ladies growing up in Jombang. The sample size was 60 and was purposely sampled. The independent variable in this study is the image of the body expressed by an image scale of the body, while the dependent variable is self-esteem which is also expressed by an self-esteem scale. The data analysis used is Product Moment Correlation analysis. The results of the analysis show that the correlation coefficient is 0.179 with p=0.000 (p > 0.05). This means that the relationship between body image and self-esteem does not exist.